Nineteenth-Century Transcriptions of Works by Fryderyk Chopin - Literska, Barbara (2020)
This book is the first monographic study of nineteenth-century transcriptions of Chopin's music. The work is based on the quantitatively and qualitatively rich source material, which formed the basis for considerations from the perspective of social history, music analysis and aesthetics. Thanks to these multiple perspectives, as well as the time range and the source base, this study may contribute to the history of the reception of Chopin's work in nineteenth-century culture; it may also prove significant in overcoming the attitude that aesthetically deprecates transcriptions and in adopting a different stance, regarding such adaptations as valuable texts of musical culture.